2018
DOI: 10.1002/glia.23315
|View full text |Cite
|
Sign up to set email alerts
|

N‐myc downstream‐regulated gene 2 protects blood–brain barrier integrity following cerebral ischemia

Abstract: Disruption of the blood-brain barrier (BBB) following cerebral ischemia is closely related to the infiltration of peripheral cells into the brain, progression of lesion formation, and clinical exacerbation. However, the mechanism that regulates BBB integrity, especially after permanent ischemia, remains unclear. Here, we present evidence that astrocytic N-myc downstream-regulated gene 2 (NDRG2), a differentiation- and stress-associated molecule, may function as a modulator of BBB permeability following ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…Increasing or rescuing the expression of NDRG2 in WT and Ndrg2 −/− mice significantly reduces the infarct volume, neurological outcome, and interstitial glutamate levels, suggesting a potentially therapeutic target for brain ischemia. A recent study reported that the loss of NDRG2 increases astrocytic MMP activity and BBB permeability, which exacerbate subsequent brain damage after permanent focal cerebral ischemia [45]. This is consistent with the function of NDRG2 as a neuroprotective protein observed in the present study, although we focused on astrocyte-mediated glutamate uptake but not astrocyteassociated blood cell infiltration and BBB permeability.…”
Section: Discussionsupporting
confidence: 92%
“…Increasing or rescuing the expression of NDRG2 in WT and Ndrg2 −/− mice significantly reduces the infarct volume, neurological outcome, and interstitial glutamate levels, suggesting a potentially therapeutic target for brain ischemia. A recent study reported that the loss of NDRG2 increases astrocytic MMP activity and BBB permeability, which exacerbate subsequent brain damage after permanent focal cerebral ischemia [45]. This is consistent with the function of NDRG2 as a neuroprotective protein observed in the present study, although we focused on astrocyte-mediated glutamate uptake but not astrocyteassociated blood cell infiltration and BBB permeability.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have demonstrated that the tumor suppressor NDRG2 has a neuroprotective function in various diseases ( 29 , 30 ). Therefore, the present study investigated whether NDRG2 was involved in the regulation of cerebral ischemic injury and necroptosis.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, NDRG2 was implicated in the ischemic stress response in several in vivo and in vitro studies [72][73][74][75][76][77][78]. Temporal and spatial patterns of NDRG2 expression in the rat brain were investigated after transient middle cerebral artery occlusion and reperfusion.…”
Section: Ndrg2 In Brain Tumors and Other Nervous System Diseasesmentioning
confidence: 99%